Expanded FDA regulation of health and wellness apps - Kasperbauer, T. J. (Bioethics, 2020)
This paper argues that the Food and Drug Administration’s (FDA) policy for health and wellness apps is ethically problematic. Currently, the FDA does not regulate health and wellness apps that are not intended for medical use. As a result of this hands-off policy, preventing harm to consumers is left primarily to developers and app marketplaces. We argue that the FDA’s duties to prevent harm and maintain accountability to the American public require that they play a much stronger role. We also discuss concerns about efficiency and fostering innovation, and argue that while they should help shape FDA regulation of health and wellness apps, they do not justify complete absence of FDA involvement.